A KAP study on acceptance of millets in diet among housewives residing in a Military Garrison - Thorikonda, Kartheek; Banerjee, Indrayudh; Veer, Prakash; Shyamsundar, K.; Mehrotra, Sameer; Sinha, Subhralok (International Journal of Research in Medical Sciences, 2024)
Background: Millets are a group of small-seeded grasses that are cultivated as food crops around the world especially in Africa and Asia. Millets have high fibre content which helps in better digestion and relief from constipation, high antioxidant activities and also helps to lower cholesterol. United Nations declared the year 2023 as International Year of Millets (IYoM-2023). Limited studies have been conducted on the Knowledge, Attitude and Practices (KAP) on acceptance to use millets in diet in our country. Consumption of millets was higher in the states of Gujarat, Karnataka, Maharashtra but negligible in the states of Kerala, Orissa, West Bengal and Tamil Nadu where rice is the most consumed cereal as opined by National Nutrition Monitoring Bureau. The objective of the study was to assess the acceptance of millets in diet among housewives residing in a Military garrison in West Bengal. Methods: A cross-sectional study was carried out from 01 Aug 2023 and 15 Aug 2023 among housewives residing in a Military garrison in West Bengal. Results: A total of 209 respondents participated in the study of which, 33% of the respondents belonged to 25-29 yrs age group. 52% of them were either graduates or post graduates. There is a significant (p<0.05) association between level of education and knowledge of health benefits of millets. Conclusions: The Armed Forces have been the front runners in incorporating millets in their ration scale as clearly observed from our present study. Sustained efforts are required to create awareness and improve acceptance of use of millets amongst general population.